Abundantly more. : The Theological Promise of the Arts in a Reductionist World. - de Gruchy, John W (Stellenbosch Theological Journal, 2024)
Abundantly More is far more than another monograph on theology and the arts, or a dummy’s guide to theological aesthetics. It is a Christian apologia in the classical sense – a carefully reasoned and theologically astute response to a world struggling for abundant life but seduced by the reductionist consequences of secularism and scientism. But, argues Begbie, “there is more to the world than we will ever be able to account for, more than could ever be fully discovered, thought, or spoken.” This “more” is beyond philosophical proof; it is discerned by the theological insight that it arises “from the sustaining presence of the infinitely living God”, that is “from the world’s being upheld by a limitless plenitude of meaning and significance.” (p. 177)